Effect of Solution Temperature on Microstructure and Mechanical Properties of Ti–5Al5Mo5V3Cr1Zr Alloy. Issue 5 (24th April 2022) - Huang, Feiyu; Huang, Chaowen; Wan, Mingpan; Xin, Shewei; Zhao, Yongqing; Wang, Tao; Ji, Shengli; Zeng, Weidong
Abstract : The work aims to reveal relationship between solution temperature, microstructure, and mechanical properties of Ti–5Al5Mo5V3Cr1Zr (Ti‐55 531) alloy. The alloys are prepared via solution processing in a temperature ranging from T β  − 100 °C (where T β is β‐transus temperature) to T β  + 100 °C for 2 h; and then air cooled, aged at 600 °C for 6 h, and air cooled again. Results indicate that solution temperature range (from T β  − 100 °C to T β  + 100 °C) can be divided into following five ranges according to performance of Ti‐55 531 alloy. The alloy presents excellent mechanical performance combining high strength and good ductility for solution temperatures ranging from T β  − 50 °C to T β  − 30 °C and from T β  + 10 °C to T β  + 30 °C. Interestingly, the Ti‐55 531 alloy exhibits a dramatically enhanced strength, while ductility drops rapidly as solution temperature exceeds T β  + 70 °C. The enhanced strength's main reason is that grain boundary α phase changes from continuous to discontinuous with increasing solution temperature; nevertheless, the increased size of β grains results in a reduction in ductility. Thus, continuity of grain boundary α phase has a dramatical influence on performance of Ti‐55 531 alloy. Abstract : The GB α films gradually change from continuous to discontinuous with increasing solution temperature as the solution temperature is above 900 °C, which enhances strength of the alloy. Thus, the continuity of grain boundary α phase has a dramatical influence on the performance of Ti‐55 531 alloy with lamellar microstructure.